Influence of Cathode Porosity on High Performance Protonic Ceramic Fuel Cells with PrBa0.5Sr0.5Co1.5Fe0.5O5-δ Cathode. Issue 13 (6th October 2018) - Seong, Arim; Kim, Junyoung; Kim, Jeongwon; Kim, Seona; Sengodan, Sivaprakash; Shin, Jeeyoung; Kim, Guntae
Abstract : Protonic ceramic fuel cells (PCFCs) are attractive energy conversion systems at intermediate operating temperatures (500–650°C) because of the low activation energy for proton conduction. Despite this advantage, the efficient operation of PCFCs is still limited partly due to the large cathodic polarization resistance. To decrease the large cathodic polarization, the modification of cathode microstructure could be an effective way because the PCFC cathode microstructure requires both sufficient pathways for oxygen supply and water vapor removal, along with a large surface area for electrochemical reactions. Herein, the correlation between the cathode microstructure and the electrochemical performance is investigated based on BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3−δ (BZCYYb) electrolyte under the PCFC operating condition at 650°C. Four cells with PrBa0.5 Sr0.5 Co1.5 Fe0.5 O5-δ (PBSCF) cathode of different porosity with identical anode/electrolyte configuration were fabricated and tested. Interestingly, the modification of cathode porosity effectively decreases the cathodic polarization resistance from 0.077 to 0.048 Ω cm 2 at 650°C, and the corresponding maximum power density of PCFCs is improved from 1.23 to 1.62 W cm − 2 . The influence of other microstructural factors such as grain size, specific surface area (per volume), and porosity in the cathode should be studied to fully understand the impacts of microstructure on the cathode performance of PCFC.